Strain effects on insulator-to-metal transition and electronic structure in VO2 - Sahu, S. R.; Majid, S. S.; Tripathy, A.; Bano, N.; Ahad, A.; Lee, Hyungwoo; Sathe, V. G.; Shukla, D. K. (Physical Review B, 2024)
Tunability of near-room temperature insulator-to-metal transition (IMT) of VO2 is a prerequisite for its applications in switching and sensing devices. IMT in VO2 is accompanied with structural transition, monoclinic (insulating) to rutile (metallic), where the V-V dimer of the monoclinic phase becomes equidistant in the rutile phase. Tuning of the V-V dimer distances can result in dramatic changes in IMT characteristics. However, understanding of such processes has been limited due to intrigued relations between structure, electronic structure, and IMT of VO2. By utilizing the substrate and Cr doping-induced strain, we have grown VO2 thin films with distinct V-V dimers, which has enabled us to study the effect of these dimers on the structure, IMT, and electronic structures of VO2. In addition to the usual M1 phase of VO2, strain-mediated T and M2 phases have been stabilized with the help of both Cr doping and tensile strain along the cR axis. We have observed that a small compressive strain (≈0.19%) along the cR axis (≈monoclinicaM axis) lowers the transition temperature significantly (by ≈10°C) compared to bulk. Temperature-dependent Raman spectroscopy measurement is used to track the exact structural transformation route followed by these insulating phases of VO2. Dependent on the nature of strain along the cR axis, IMT temperature is found to vary - increases (for tensile) or decreases (for compressive) - while Cr doping-induced strain has a less significant impact on the IMT temperature compared to the nature of the strain. X-ray absorption near-edge spectroscopy (XANES) has been utilized to examine the electronic structure of the grown VO2 thin films. Temperature variation of pre-edge features (vanadium 3d orbitals) in XANES directly scales with the insulator-to-metal transition, which suggests that the electronic structure of VO2 is strongly influenced by the nature (compressive/tensile) of strain, whereas minimal changes in electronic structure have been observed due to different insulating phases (M1, T, and M2). Our study underscores the important role of the nature of strain in tailoring the IMT in VO2.
Keywords: Cr-doping; Electronic.structure; Induced strain; Insulating phase; Insulator-to-metal transitions; Metal transition temperature; Transition structures; V/V; VO2 thin film; X-ray absorption near edge spectroscopy